Pemanfaatan Gadget dan Hubunganya dengan Sikap Anak-Anak - Misra Misra; Rika Maria; Mesi Gusni Putri (Universitas Islam Negeri Imam Bonjol Padang, 2023)
Utilization of gadgets among children in the Lambung Bukit environment. Children use gadgets not for learning purposes but for playing games such as free fire, mobile legends which can have negative behavioral impacts such as children being undisciplined, spending a lot of time with gadgets, often not praying and not focused on studying. This research focuses on the issue of gadget use and its relationship with children's attitudes in the Lambung Bukit neighborhood, Puah, Padang City. Research objectives (1) To determine the use of gadgets in children (2) To determine the efforts made by parents in controlling the use of gadgets on children's behavior (3) To explain the relevance of gadget use to children's attitudes. This research method is qualitative. The informants for this research were parents, children and the village head of Lambung Bukit Village, Pauh District, Padang City. Data collection techniques are observation, interviews, and documentation. This data analysis technique is data reduction, data presentation, drawing conclusions/verification. The results of the research conclude that, (1) Children use gadgets to play games such as free fire, mobile legends which do not support learning (2) Parents control children who play with smartphones get angry, grumble, give reprimands and some also take gadgets at certain hours when it is late at night, when it is study time and prayer time (3) Looking at the use of gadgets among children, it is very relevant to behavior children because of the impact of these gadgets, including children becoming disobedient, slow to respond, forgetting to eat and pray, or even not listening to what their parents say because they are busy playing with gadgets.